Differential Object Marking in Spanish: state of the art - Fábregas, Antonio (Borealis – An International Journal of Hispanic Linguistics, 2013)
This state of the art tries to cover as much as possible about the properties, conditions and analyses of Differential Object Marking (DOM) in Spanish. Starting with some considerations about the boundaries of the phenomenon, it considers its morphological, semantic and syntactic properties –with respect both to the internal properties of the direct object and to the wider context in which it appears–. It also reviews the other morphosyntactic phenomena that have been claimed to correlate with DOM, and finally goes through a number of analysis in different theoretical traditions to highlight the points of agreement and debate in the current literature.